Security dilemma of a small state / Part Two - Internal Crisis and External Intervention in Sri Lanka - Jayasekera, P. V. J.; Institute for International Studies (Peradeniya, Sri Lanka) (New Delhi, India : South Asian Publishers Kandy , Sri Lanka : Institute for International Studies, 1995)
Research conducted by the Institute for International Studies, Peradeniya, Sri Lanka.
pt. 2. Internal crisis and external intervention in Sri Lanka.
Includes index.
Includes bibliographical references.
Keywords: National security -- Sri Lanka; Sri Lanka -- Politics and government -- 1978-; South Asia -- Politics and government